ASSESSING THE LEVEL OF AWARENESS AND EXTENT OF PARTICIPATION OF WOMEN IN NGO ACTIVITIES IN UNITED ANDHRA PRADESH - K.S. PURNIMA (The Journal of Research ANGRAU, 2016)
The study was conducted in the three regions of Andhra Pradesh i.e., coastal Andhra, Telangana and Rayalaseema with a sample size of 150 women beneficiaries of 15 selected NGOs. Exploratory research design was adopted. For the purpose of this study, the level of awareness of women on different developmental programmes of NGOs and the extent of participation of women in these activities was assessed. The findings are presented region wise and activity wise. The salient findings of the study are that for all the NGO activities, majority of the women had fallen under medium category in the three regions with respect to level of awareness on different NGO programmes. The overall findings also revealed that with regard to participation in NGO activities in coastal Andhra region majority fell under medium(52%) followed by high(32%) and low(16%) category. In Telangana, similar trend was observed with majority falling under medium(50%) followed by high(28%) and low(22%) category. In Rayalaseema, majority fell under medium (51%) followed by high (30%) and low (19%) category with regard to participation in NGO activities.